Hematological parameters in pediatric pulmonary and extrapulmonary tuberculosis in Vietnam: a prospective observational study - Chau Duc Nguyen-Huu; Thi Hanh Chan Tran; Thi Hong Nhung La; Van-Tuy Nguyen (Egyptian Pediatric Association Gazette)
Abstract Background Tuberculosis in children remains a significant public health issue in Vietnam. This study aims to describe the clinical and paraclinical characteristics of children with pulmonary and extrapulmonary tuberculosis and to evaluate the value of certain hematological parameters in differentiating between these two forms. Methods This prospective observational study was conducted on 36 children diagnosed and treated for tuberculosis at Hue Central Hospital. Clinical and paraclinical characteristics were compared between pulmonary and extrapulmonary tuberculosis. The ROC curve, sensitivity, and specificity were used to compare the diagnostic value of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and Systemic Immune-Inflammation Index (SII) in differentiating pulmonary from extrapulmonary tuberculosis. Results Of the 36 children with tuberculosis in the study group, 58.3% had pulmonary tuberculosis and 41.7% had extrapulmonary tuberculosis. There were significant differences between pulmonary and extrapulmonary tuberculosis in terms of gender distribution (p = 0.037), family history (p = 0.008), fever (p = 0.001), malnutrition (p = 0.008), and night sweats (p = 0.027). Pulmonary tuberculosis had significantly higher levels of inflammatory markers such as white blood cells, neutrophils, ESR, and CRP compared to extrapulmonary tuberculosis. The NLR and SII indices showed good discriminatory value, while the PLR index showed acceptable discriminatory value when comparing pulmonary and extrapulmonary tuberculosis. The SII index had the best diagnostic value with an AUC of 0.832, sensitivity of 66.7%, and specificity of 86.7%. Conclusions Hematological indices calculated from the complete blood count (NLR, PLR, SII) have good value in differentiating between pulmonary and extrapulmonary tuberculosis in children, with the SII index having the best value.